Systematic Literature Review: Pentingnya Penggunaan Media Pembelajaran Dalam Meningkatkan Minat Belajar Siswa Sekolah Dasar - Yulina Desri Hariaty; Sahrun Nisa; Ari Suriani (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is a systematic literature review focusing on the importance of using instructional media to enhance elementary school students' interest in learning. The method used is an analysis of nine accredited national journal articles relevant to the topic. The results show that the use of instructional media plays a crucial role in increasing elementary school student’s interest in learning. Instructional media can make abstract concepts more concrete, reduce verbalism, direct intuition, and motivate students to learn. Additionally, instructional media can increase active student engagement, create a pleasant learning atmosphere, and facilitate an easier understanding of the material. A combination of conventional methods and innovative instructional media has proven effective in enhancing elementary school students' cognitive interest in learning